Positive electrode active material, positive electrode, and lithium secondary battery

JP2025036591AActive Publication Date: 2025-03-14ECOPRO BM CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024229586
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-10-27
Filing Date
2024-12-26
Publication Date
2025-03-14
Estimated Expiration
2043-05-29

AI Technical Summary

Benefits of technology

【0048】 本発明によれば、商用化されたニッケル-コバルト-マンガン(NCM)またはニッケル-コバルト-アルミニウム(NCA)組成の3元系リチウム複合酸化物と比較するとき、電気化学的特性および/または安定性の観点から様々な不利な部分がある従来のリチウム過剰のリチウムマンガン系酸化物の限界を改善することが可能である。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025036591000001
    Figure 2025036591000001
  • Figure 2025036591000002
    Figure 2025036591000002
  • Figure 2025036591000003
    Figure 2025036591000003
Patent Text Reader

Abstract

To provide a positive electrode active material capable of rapidly reducing a battery performance by a side reaction at the time of an initial battery reaction under a high-voltage condition.SOLUTION: In a positive electrode active material containing a lithium manganese system oxide in which a phase belonged to a C2 / m space group and a phase belonged to a R3-m space group are solid-dissolved or mixed, the lithium manganese system oxide contains a secondary particle formed by condensing a plurality of primary particles. At least one part of oxygen existed in the lithium manganese system oxide is replaced with halogen, and a short-shaft length measured to each primary particle exposed to a front surface of each secondary particle is larger than 75nm, and is 500nm or less. In the positive electrode active material, a barrier layer covering at least one part of each primary particle and each secondary particle exists.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a positive electrode active material, a positive electrode, and a lithium secondary battery including the same. More specifically, the present invention relates to a positive electrode active material including a lithium-excess lithium-manganese-based oxide, which prevents a decrease in electrochemical characteristics of a lithium secondary battery, including rate characteristics, caused by excess lithium and manganese present in the lithium manganese-based oxide, by inducing growth of primary particles constituting the lithium manganese-based oxide, and in particular, to a positive electrode active material, a positive electrode, and a lithium secondary battery including the same, which are capable of preventing deterioration in the life span of a lithium secondary battery by reducing side reactions between the lithium manganese-based oxide and an electrolyte during high-voltage operation and suppressing or mitigating elution of transition metals from the lithium manganese-based oxide. [Background technology]

[0002] Batteries store electricity by using materials capable of electrochemical reaction at the positive and negative electrodes. A representative example of such batteries is a lithium secondary battery, which stores electrical energy by the difference in chemical potential when lithium ions are intercalated / deintercalated at the positive and negative electrodes.

[0003] The lithium secondary battery is manufactured by using a material capable of reversible intercalation / deintercalation of lithium ions as a positive electrode active material and a negative electrode active material, and filling an organic electrolyte or a polymer electrolyte between the positive electrode and the negative electrode.

[0004] Representative materials used as positive electrode active materials for lithium secondary batteries include lithium composite oxides, such as LiCoO2, LiMn2O4, LiNiO2, LiMnO2, and oxides of Ni, Co, Mn, Al, etc.

[0005] Among the positive electrode active materials, LiCoO2 is the most widely used because of its excellent life characteristics and charge / discharge efficiency. However, it has a drawback in that it is expensive due to the limited availability of cobalt as a raw material, and therefore has limited price competitiveness.

[0006] Lithium manganese oxides such as LiMnO2 and LiMn2O4 have the advantages of being thermally safe and inexpensive, but have problems with small capacity and poor high-temperature characteristics. In addition, LiNiO2-based positive electrode active materials show high discharge capacity battery characteristics, but are difficult to synthesize due to the problem of cation mixing between Li and transition metals, which causes major problems with rate characteristics.

[0007] In addition, a large amount of Li by-products are generated depending on the depth of the cation mixing. The Li by-products mostly contain LiOH and Li2CO3, which may cause gelation during the preparation of the positive electrode paste or gas generation due to repeated charging and discharging after the electrode is manufactured. In addition, the remaining Li2CO3 among the Li by-products increases the swelling phenomenon of the cell, thereby reducing the life characteristics.

[0008] To overcome these shortcomings of conventional positive electrode active materials, various candidate materials have been proposed.

[0009] For example, research is being conducted to use lithium-rich lithium manganese oxides, which contain an excess amount of Mn among transition metals and have a lithium content greater than the total content of the transition metals, as a positive electrode active material for lithium secondary batteries. Such lithium-rich lithium manganese oxides are also called overlithiated layered oxides (OLO).

[0010] Although OLO has an advantage of theoretically being able to exhibit high capacity under a high voltage operating environment, in practice, it has a disadvantage of having relatively low electrical conductivity due to the excessive amount of Mn contained in the oxide, which results in low rate characteristics of lithium secondary batteries using OLO. Such low rate characteristics cause problems such as reduced charge / discharge capacity and life efficiency (capacity retention) during charge / discharge cycles of the lithium secondary battery.

[0011] In addition, the decrease in charge / discharge capacity or voltage decay during charge / discharge cycles of a lithium secondary battery using OLO may be induced by a phase transition caused by the movement of transition metals in the lithium manganese oxide. For example, when a phase transition is induced by the movement of transition metals in an unintended direction in a lithium manganese oxide having a layered crystal structure, a spinel or similar crystal structure may be formed entirely and / or partially in the lithium manganese oxide.

[0012] In order to solve the above problems, research has been conducted into modifying the composition of OLO, but these attempts have not yet reached a commercial level. Summary of the Invention [Problem to be solved by the invention]

[0013] In the lithium secondary battery market, the growth of lithium secondary batteries for electric vehicles is playing a leading role in the market, and as a result, the demand for positive electrode active materials used in lithium secondary batteries is also continuously increasing.

[0014] For example, in the past, lithium secondary batteries using lithium iron phosphate (LFP) were mainly used from the perspective of ensuring safety, but recently there has been a trend toward expanding use of nickel-based lithium composite oxides, which have a larger energy capacity per weight than LFP.

[0015] In addition, nickel-based lithium composite oxides, which are currently mainly used as positive electrode active materials for high-capacity lithium secondary batteries, essentially use ternary metal elements such as nickel, cobalt, and manganese or nickel, cobalt, and aluminum. However, since the supply and demand of cobalt is unstable and it is excessively expensive compared to other raw materials, a new positive electrode active material with a reduced or eliminated cobalt content is needed.

[0016] Considering these various circumstances, lithium-excess lithium manganese-based oxides can meet the above-mentioned market expectations, but the lithium manganese-based oxides still have limitations in that their electrochemical properties and stability are insufficient as an alternative to commercialized positive electrode active materials such as nickel-cobalt-manganese (NCM) or nickel-cobalt-aluminum (NCA) ternary lithium composite oxides.

[0017] For example, when a transition metal in a lithium manganese-based oxide moves in an unintended direction, and a spinel or similar crystal structure is formed entirely and / or partially in the lithium manganese-based oxide, a decrease in charge / discharge capacity or voltage decay may occur during charge / discharge cycles of a lithium secondary battery using OLO, as described above.

[0018] However, when compared with other types of commercially available positive electrode active materials, the conventional lithium-excess lithium manganese-based oxide has disadvantages in terms of electrochemical properties and / or stability. However, the present inventors have confirmed that the lithium-excess lithium manganese-based oxide can also exhibit electrochemical properties and stability at a level that allows it to be commercially used, by making the primary particles constituting the lithium manganese-based oxide have a different shape from conventional ones.

[0019] Accordingly, the present invention provides a positive electrode active material including a lithium-excess lithium-manganese-based oxide, in which the primary particles constituting the lithium manganese-based oxide are induced to grow in a selective direction, so that the primary particles constituting the lithium manganese-based oxide have a different shape from that of known lithium manganese-based oxides.

[0020] In particular, the present invention aims to provide a cathode active material capable of reducing the specific surface area of ​​the lithium manganese-based oxide by inducing crystal growth or particle growth of primary particles constituting the lithium manganese-based oxide, thereby preventing a rapid decrease in battery performance due to side reactions during an initial battery reaction under high voltage conditions.

[0021] Another object of the present invention is to provide a cathode active material capable of mitigating the decrease in diffusibility of lithium ions through the primary particles as the size of the primary particles increases by enabling the primary particles to undergo crystal growth or particle growth in a selective direction.

[0022] The inventors have confirmed that lithium manganese oxides are more likely to have transition metals eluted from the particle surface by repeated charging and discharging than ternary lithium composite oxides. In particular, there is a high possibility that Mn contained in an excess amount in lithium manganese oxides will elute from the particle surface.

[0023] When a transition metal is dissolved from the lithium manganese-based oxide, the dissolved transition metal may react with an electrolyte on the surface of the lithium manganese-based oxide to form impurities. The impurities not only increase the surface resistance of the lithium manganese-based oxide, but also act as a cause of reducing the intercalation / deintercalation efficiency of lithium ions through the lithium manganese-based oxide.

[0024] In addition, the transition metal dissolved from the lithium manganese-based oxide or impurities formed by the reaction of the dissolved transition metal with the electrolyte can move to the negative electrode using the electrolyte as a medium and can be deposited on the surface of the negative electrode.

[0025] For example, a side reaction occurs between the surface of the lithium manganese oxide and the electrolyte, or the lithium manganese oxide undergoes a structural change (such as a change in crystal structure) that causes excessive Mn contained in the lithium manganese oxide to be dissolved. 2+ The Mn dissolved in the electrolyte can be dissolved in the electrolyte. 2+ During formation or charging / discharging, Mn can move to the surface of the negative electrode using the electrolyte as a medium and react with various substances (electrons, electrolyte, electrodes, by-products, etc.) present in the battery, resulting in the formation of Mn on the surface of the negative electrode. 2+ , Mn will be present as impurities including metal or Mn-containing compounds (e.g., MnCO3, MnO, MnF2, etc.).

[0026] Transition metals or impurities deposited on the surface of the negative electrode can rapidly increase the resistance of the negative electrode, and such an abnormal resistance phenomenon is a typical cause of accelerating the deterioration of the life of a lithium secondary battery.

[0027] In particular, in the case of a lithium secondary battery using the lithium manganese-based oxide as a positive electrode active material, the operating voltage is higher than that of a lithium secondary battery using other commercially available ternary lithium composite oxides as a positive electrode active material, and therefore, is vulnerable to the above-mentioned problems.

[0028] However, currently there is no technology to solve the problem of transition metal elution from lithium-rich lithium manganese oxides and the associated problems.

[0029] As described above, compared to other types of commercially available positive electrode active materials, conventional lithium-excess lithium manganese-based oxides have disadvantages in terms of electrochemical properties and / or stability. However, the present inventors have confirmed that lithium-excess lithium manganese-based oxides can also exhibit electrochemical properties and stability at a level that allows them to be commercially used by providing a barrier layer that can suppress or reduce the elution of transition metals from the surface of the lithium manganese-based oxide while controlling the bulk composition of the lithium manganese-based oxide.

[0030] Accordingly, an object of the present invention is to provide a positive electrode active material containing a lithium-excess lithium-manganese-based oxide, which is capable of forming a barrier layer on the surface of the lithium-manganese-based oxide to suppress or mitigate the elution of a transition metal from the lithium-manganese-based oxide.

[0031] Another object of the present invention is to provide a lithium secondary battery that can prevent deterioration in electrochemical characteristics of a lithium secondary battery, including rate characteristics, caused by excessive amounts of lithium and manganese conventionally present in OLO, by using a positive electrode including the positive electrode active material defined herein, and can achieve high stability by reducing side reactions between the positive electrode active material and an electrolyte during high voltage operation. [Means for solving the problem]

[0032] According to one aspect of the present invention for solving the above-mentioned technical problems, there is provided a positive electrode active material including a lithium manganese-based oxide in which a phase belonging to the C2 / m space group and a phase belonging to the R3-m space group are dissolved or combined.

[0033] Generally, commercially available ternary lithium composite oxides having a nickel-cobalt-manganese (NCM) or nickel-cobalt-aluminum (NCA) composition have a single phase of a phase belonging to the R3-m space group, whereas the lithium-rich lithium manganese oxide defined in this application is characterized by a solid solution or composite of a phase belonging to the C2 / m space group and a phase belonging to the R3-m space group.

[0034] In an embodiment, the lithium manganese-based oxide includes secondary particles formed by agglomeration of a plurality of primary particles.

[0035] In this case, by doping the oxide precursor of the lithium manganese-based oxide with a halogen while inducing crystal growth or particle growth of the primary particles during firing of the oxide precursor of the lithium manganese-based oxide, the average minor axis length of the primary particles constituting the lithium manganese-based oxide may be 130 nm or more, preferably 130 nm or more and less than 400 nm.

[0036] Furthermore, the proportion of primary particles having a minor axis length of 100 nm or more among 20 primary particles selected in order of longest minor axis length from among the primary particles exposed on the surface of the secondary particle from an SEM image of the secondary particle may be greater than 80% and less than 100%.

[0037] The average minor axis length of the primary particles can be measured for the primary particles exposed on the surface of the secondary particles from the SEM image of the secondary particles (for example, calculated from 20 primary particles selected in order of the longest minor axis length from among the primary particles exposed on the surface of the secondary particles from the SEM image of the secondary particles).

[0038] A barrier layer may be present on at least a portion of the surface of the primary particles and / or the secondary particles, which can suppress or reduce the elution of transition metals from the primary particles and / or the secondary particles.

[0039] A grain boundary is defined between adjacent primary particles in the secondary particle, and the barrier layer may be present along the grain boundary in a diffused state from a surface portion of the secondary particle toward a center portion of the secondary particle.

[0040] In one embodiment, the lithium manganese-based oxide may be represented by the following Formula 1:

[0041] [Chemical formula 1] Li (Li a M1 x M2 y )O 2-b X b (where: M1 is at least one selected from Ni and Mn; M2 is at least one selected from Ni, Mn, Co, Al, P, Nb, B, Ti, Zr, Ba, K, Mo, Si, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, V, Ta, Sn, Hf, Ce, Gd, and Nd, and M2 does not overlap with M1; X is a halogen capable of substituting at least a portion of the oxygen present in the lithium manganese oxide; 0 <a≦0.7、0<b≦0.1、0<x≦1、0≦y<1、0<x+y≦1である)

[0042] In another embodiment, the lithium manganese-based oxide may be represented by the following formula 1-1:

[0043] [Chemical formula 1-1] rLi2MnO 3-b″ X′ b″ (1-r)Li a′ M1 x′ M2 y′ O 2-b′ X b′ (where: M1 is at least one selected from Ni and Mn; M2 is at least one selected from Ni, Mn, Co, Al, P, Nb, B, Ti, Zr, Ba, K, Mo, Si, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, V, Ta, Sn, Hf, Ce, Gd, and Nd, and M2 does not overlap with M1. X and X′ are halogens capable of substituting at least a part of the oxygen present in the lithium manganese-based oxide. 0 < r ≤ 0.7, 0 < a′ ≤ 1, 0 ≤ b′ ≤ 0.1, 0 ≤ b″ ≤ 0.1, 0 < x′ ≤ 1, 0 ≤ y′ < 1, 0 < x′ + y′ ≤ 1, provided that b′ and b″ are not both 0 at the same time.

[0044] At least a part of the oxygen present in the lithium manganese-based oxide may be substituted with a halogen, preferably fluorine. Specifically, the primary particles may be doped with fluorine.

[0045] During the firing of the oxide precursor of the lithium manganese-based oxide, it is preferable that a halogen (for example, fluorine) is doped into the primary particles while inducing crystal growth and particle growth of the primary particles.

[0046] According to another aspect of the present invention, a positive electrode including the above-described positive electrode active material is provided.

[0047] According to still another aspect of the present invention, a lithium secondary battery using the above-described positive electrode is provided.

Advantages of the Invention

[0048] According to the present invention, when compared with commercialized ternary lithium composite oxides having a nickel-cobalt-manganese (NCM) or nickel-cobalt-aluminum (NCA) composition, it is possible to improve the limitations of conventional lithium-excess lithium manganese-based oxides that have various disadvantages from the viewpoints of electrochemical characteristics and / or stability.

[0049] Specifically, the lithium manganese-based oxide according to the present invention includes primary particles in which crystal growth or particle growth is induced in a selective direction, and the primary particles have a different shape from known lithium manganese-based oxides due to the selective growth of the primary particles.

[0050] First, when inducing crystal growth or particle growth of the primary particles constituting the lithium manganese-based oxide, the specific surface area of ​​the lithium manganese-based oxide can be reduced, thereby preventing a rapid decrease in battery performance due to side reactions during the initial battery reaction under high voltage conditions.

[0051] When the specific surface area of ​​the lithium manganese-based oxide is reduced, it is possible to reduce side reactions between the lithium manganese-based oxide and the electrolyte. In particular, OLO, such as the lithium manganese-based oxide, has an advantage of exhibiting high capacity under a high voltage operating environment, but the possibility of side reactions between the lithium manganese-based oxide and the electrolyte may increase as the operating voltage increases, so it is important to reduce side reactions between the lithium manganese-based oxide and the electrolyte.

[0052] Therefore, the side reaction between the lithium manganese-based oxide and the electrolyte is reduced, thereby improving the stability and life span of a lithium secondary battery using the lithium manganese-based oxide as a positive electrode active material. In particular, the positive electrode active material in which the side reaction with the electrolyte is suppressed can operate a lithium secondary battery at a higher voltage. In addition, as described above, when the growth of the primary particles is induced, the specific surface area of ​​the lithium manganese-based oxide is reduced, thereby reducing side reactions during the initial battery reaction under high voltage conditions. However, as the primary particles grow, the diffusion path of lithium ions in the primary particles becomes longer. This reduces the diffusibility of lithium ions through the primary particles, which ultimately causes an increase in the resistance of the lithium manganese-based oxide.

[0053] According to the present invention, the primary particles constituting the lithium manganese-based oxide can be allowed to undergo crystal growth or particle growth in a selective direction, thereby providing an advantage in that it is possible to alleviate the decrease in diffusibility of lithium ions through the primary particles as the size of the primary particles increases.

[0054] In addition, by forming a barrier layer on the surface of the lithium manganese-based oxide, it is possible to suppress or reduce the elution of a transition metal from the lithium manganese-based oxide, thereby preventing the transition metal eluted on the surface of the lithium manganese-based oxide from reacting with an electrolyte to form impurities.

[0055] The transition metals dissolved from the lithium manganese-based oxide and / or impurities formed by the reaction of the dissolved transition metals with the electrolyte can migrate to the negative electrode using the electrolyte as a medium, and the impurities can be deposited on the surface of the negative electrode, causing a sudden increase in the negative electrode resistance. Therefore, as described in the present invention, it is necessary to restrict the unintended migration of transition metals in the lithium secondary battery.

[0056] That is, according to the present invention, by preventing the elution of the transition metal from the lithium manganese-based oxide, it is possible to prevent the accelerated deterioration of the life of the lithium secondary battery caused by the elution of the transition metal from the lithium manganese-based oxide and the deposition of impurities in the positive electrode and / or negative electrode.

[0057] In this manner, when a positive electrode including the positive electrode active material defined in the present application is used, it is possible to prevent the deterioration of electrochemical characteristics of a lithium secondary battery, including rate characteristics, caused by excess lithium and manganese conventionally present in OLO, and to achieve high stability by reducing side reactions between the positive electrode active material and an electrolyte during high voltage operation.

[0058] The specific effects of the present invention, together with the above-mentioned effects, will be described below while explaining specific matters for carrying out the invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0059] In order to make the present invention easier to understand, certain terms are defined herein for convenience. Unless otherwise defined herein, scientific and technical terms used in the present invention shall have the meanings commonly understood by those of ordinary skill in the art. Furthermore, unless otherwise specified by the context, singular terms shall be understood to include their plural forms, and plural terms shall be understood to include their singular forms.

[0060] Hereinafter, a positive electrode active material including a lithium-excess lithium manganese-based oxide according to some embodiments of the present invention and a lithium secondary battery including the positive electrode active material will be described in more detail.

[0061] positive electrode active material According to one aspect of the present invention, there is provided a positive electrode active material comprising a lithium manganese-based oxide in which a phase belonging to the C2 / m space group and a phase belonging to the R3-m space group are dissolved or combined.

[0062] The lithium manganese-based oxide contains at least lithium, nickel, and manganese. In this case, the lithium manganese-based oxide is also called an overlithiated layered oxide (OLO) because the lithium content in the lithium manganese-based oxide is greater than the total content of other transition metals (generally, the molar ratio of lithium to all metal elements other than lithium in the lithium manganese-based oxide (Li / Metal molar ratio) is greater than 1).

[0063] In general, in a commercially available ternary lithium composite oxide having a nickel-cobalt-manganese (NCM) or nickel-cobalt-aluminum (NCA) composition, the manganese content in all metal elements excluding lithium is 20 mol % or less. In consideration of this, the lithium manganese-based oxide has a relatively high ratio of manganese (e.g., 50 mol % or more, preferably 55 mol % to 75 mol %) in all metal elements compared to a commercially available ternary lithium composite oxide.

[0064] In addition, considering that commercially available ternary lithium composite oxides having a nickel-cobalt-manganese (NCM) or nickel-cobalt-aluminum (NCA) composition have a nickel content of 60 mol% or more (80 mol% or more in the case of a high-Ni type) in all metal elements excluding lithium, the lithium manganese-based oxide has a relatively low ratio of nickel in all metal elements (for example, less than 50 mol%, preferably 25 mol% to 45 mol%) compared to commercially available ternary lithium composite oxides.

[0065] There is also a difference in that the Li / Metal molar ratio measured from the lithium manganese-based oxide defined in the present application is larger than that of ternary lithium composite oxides such as nickel-cobalt-manganese (NCM) or nickel-cobalt-aluminum (NCA). For example, the Li / Metal molar ratio of ternary lithium composite oxides such as nickel-cobalt-manganese (NCM) or nickel-cobalt-aluminum (NCA) has a value close to 1. On the other hand, the Li / Metal molar ratio of the lithium manganese-based oxide defined in the present application is larger than 1, preferably 1.1 to 1.7, more preferably 1.2 to 1.6.

[0066] Despite the above-mentioned differences in composition, the lithium manganese-based oxide can also function as a composite metal oxide capable of intercalating / deintercalating lithium ions.

[0067] The lithium manganese-based oxide included in the positive electrode active material defined herein includes secondary particles formed by agglomeration of a plurality of primary particles, and the lithium manganese-based oxide may partially exist as one primary particle, i.e., a single particle.

[0068] The primary particles constituting the lithium manganese-based oxide may have various shapes within the range defined herein, for example, the primary particles may have a plate shape, a rod shape, an elliptical shape, and / or an irregular shape.

[0069] Conventional lithium-rich lithium manganese oxides have a secondary particle form in which a plurality of primary particles are aggregated, and generally have a form in which primary particles having an average particle size of several to several tens of nm are aggregated.

[0070] On the other hand, the primary particles constituting the lithium manganese-based oxide defined in the present application may have an average particle size of 0.1 μm to 5 μm, preferably 0.1 μm to 1.0 μm, and more preferably 0.25 μm to 0.75 μm, due to the induction of crystal growth or particle growth.

[0071] The long axis length of the primary particles, the short axis length of the primary particles, the ratio of the long axis length to the short axis length of the primary particles (long axis length / short axis length), and the average particle size of the primary particles ([long axis length+short axis length] / 2) can be calculated as the average value of the long axis length and short axis length of the primary particles exposed on the surface of the secondary particles.

[0072] For example, the average value of the results measured from all primary particles exposed on the surface of the secondary particle, or the average value of the results measured from a plurality of primary particles selected from the primary particles exposed on the surface of the secondary particle (for example, or calculated from a plurality of primary particles (e.g., 10 primary particles, 20 primary particles, etc.) selected in order of the longest minor axis length from the primary particles exposed on the surface of the secondary particle from an SEM image of the secondary particle) can be used.

[0073] When the average particle size of the primary particles is less than 0.1 μm, the specific surface area of ​​the lithium manganese oxide (secondary particles) composed of the primary particles is relatively large, and in this case, the lithium manganese oxide and the electrolyte are more likely to cause a side reaction during storage or operation of the lithium secondary battery.

[0074] On the other hand, when the average particle size of the primary particles is larger than 5 μm, the growth of the primary particles is excessively induced, and the diffusion path of the lithium ions in the primary particles is also lengthened. When the diffusion path of the lithium ions in the primary particles is excessively long, the mobility of the lithium ions in the primary particles and the diffusion of the lithium ions through the primary particles are reduced, which causes the resistance of the lithium manganese oxide (secondary particles) composed of the primary particles to increase.

[0075] In order to reduce the specific surface area of ​​the lithium manganese oxide and at the same time prevent a decrease in the mobility of lithium ions within the primary particles and the diffusibility of lithium ions through the primary particles, the average particle size of the primary particles is preferably 0.1 μm to 5 μm, more preferably 0.1 μm to 1.0 μm, and even more preferably 0.25 μm to 0.75 μm.

[0076] In addition, it is not possible to accurately determine whether the growth of the primary particles is induced in a selective direction from the average particle size of the primary particles defined above. Therefore, when the primary particles constituting the lithium manganese-based oxide defined in the present application satisfy the above-mentioned range of average particle size and the below-mentioned definition of the short axis length, the specific surface area of ​​the primary particles can be effectively reduced within a range that alleviates the reduction in the diffusibility of lithium ions through the primary particles.

[0077] The minor axis length measured for the primary particles exposed on the surface of the secondary particles from an SEM image of the secondary particles may be greater than 75 nm and less than 500 nm. The minimum minor axis length measured for the primary particles exposed on the surface of the secondary particles may be greater than 75 nm, preferably greater than 90 nm. The maximum minor axis length measured for the primary particles exposed on the surface of the secondary particles may be less than 500 nm, preferably less than 450 nm.

[0078] In addition, by doping the oxide precursor with a halogen while inducing crystal growth or particle growth of the primary particles during calcination of the oxide precursor of the lithium manganese oxide, the average minor axis length of the primary particles constituting the lithium manganese oxide may be 130 nm or more, preferably 130 nm or more and less than 400 nm, more preferably 130 nm or more and 200 nm or less. As described above, the average minor axis length of the primary particles may be the average value of the results measured for all primary particles exposed on the surface of the secondary particles or a plurality of primary particles (e.g., 10 primary particles, 20 primary particles, etc.) selected in descending order of minor axis length from among the primary particles exposed on the surface of the secondary particles.

[0079] As the ratio of primary particles having a minor axis length of 75 nm or less among the primary particles exposed on the surface of the secondary particles increases, the average minor axis length of the primary particles decreases. If the number of primary particles having a minor axis length of less than 50 nm among the primary particles exposed on the surface of the secondary particles is excessively large, the average minor axis length of the primary particles may be less than 130 nm. The average minor axis length of the primary particles being less than 130 nm means that the crystal growth or particle growth of the primary particles constituting the secondary particles is generally insufficient.

[0080] When the average minor axis length of the primary particles is less than 130 nm, the specific surface area of ​​the lithium manganese-based oxide (secondary particles) composed of the primary particles becomes relatively large, and the lithium manganese-based oxide and the electrolyte are likely to cause a side reaction during storage or operation of the lithium secondary battery.

[0081] In addition, from the viewpoint of reducing the deviation in the minor axis length of the primary particles exposed on the surface of the secondary particles, the ratio of primary particles having a minor axis length of 100 nm or more measured from a plurality of primary particles (e.g., 10 primary particles, 20 primary particles, etc.) selected in order of the longest minor axis length from among all primary particles exposed on the surface of the secondary particles may be more than 80% and 100% or less, preferably 90% or more and 100% or less. The smaller the deviation in the minor axis length of the primary particles exposed on the surface of the secondary particles, the more uniform the surface kinetic of the secondary particles can be maintained.

[0082] Meanwhile, as the ratio of primary particles having a minor axis length of more than 500 nm among the primary particles exposed on the surface of the secondary particles increases, the average minor axis length of the primary particles increases. When the number of primary particles having a minor axis length of more than 500 nm among the primary particles exposed on the surface of the secondary particles becomes excessively large, the average minor axis length of the primary particles may be 400 nm or more. The average minor axis length of the primary particles being 400 nm or more means that the growth of the primary particles constituting the secondary particles is generally excessively induced.

[0083] In general, when the lithium manganese oxide is over-sintered during the preparation thereof, the growth of the primary particles may be unnecessarily promoted.When the average minor axis length of the primary particles is 400 nm or more, the primary particles are excessively induced to grow in the major axis direction, making it difficult to alleviate the decrease in the diffusibility of lithium ions through the primary particles.

[0084] When the lithium manganese-based oxide exists as secondary particles formed by agglomeration of a plurality of primary particles, the average particle size of the secondary particles ([long axis length + short axis length] / 2) may be 0.5 μm to 15 μm. The average particle size of the secondary particles may vary depending on the number of the primary particles constituting the secondary particles. In addition, as the average particle size of the primary particles increases due to induced crystal growth or particle growth of the primary particles, the number of the primary particles constituting the secondary particles may decrease.

[0085] As described above, the lithium manganese-based oxide defined in the present application is composed of primary particles in which crystal growth or particle growth is induced, thereby reducing the specific surface area of ​​the lithium manganese-based oxide, and thus alleviating the decrease in lithium ion diffusivity through the primary particles as the size of the primary particles increases. Also, the charge-transfer and / or diffusivity (i.e., surface kinetic) of lithium ions on the surface of the lithium manganese-based oxide can be prevented from decreasing.

[0086] In addition, the crystal growth or particle growth of the primary particles constituting the lithium manganese-based oxide defined herein may be induced, thereby exhibiting an overall reduced specific surface area. As a result, the lithium manganese-based oxide may achieve sufficient surface kinetics and at the same time improve surface stability, thereby reducing side reactions between the lithium manganese-based oxide and the electrolyte. As a result, early deterioration of the positive electrode active material including the lithium manganese-based oxide defined herein may be prevented, which may contribute to improving the life of a lithium secondary battery using the positive electrode active material.

[0087] The lithium manganese oxide defined in this application is 2.53m 2 More specifically, the lithium manganese oxide may have a specific surface area of ​​less than 0.52 m / g by inducing crystal growth or particle growth in a selective direction of the primary particles within a range that alleviates a decrease in the diffusibility of lithium ions mediated by the primary particles. 2 / g greater than 2.53m 2 / g, preferably less than 0.52 m 2 / g greater than 2.27m 2 / g, more preferably less than 0.65m 2 / g or more 1.20m 2 / g.

[0088] There are various methods for inducing crystal growth or particle growth of the primary particles in the lithium manganese-based oxide, but the intended effect of the present application may not be achieved depending on the difference in the method for inducing crystal growth or particle growth of the primary particles. According to the present invention, a method is used in which the oxide precursor of the lithium manganese-based oxide is doped with a halogen (specifically, fluorine) while inducing the growth of the primary particles when the oxide precursor is calcined. Even if halogen doping is induced when the hydroxide precursor of the lithium manganese-based oxide or the oxide precursor of the lithium manganese-based oxide is calcined, the intended effect of crystal growth may not be achieved, so for a detailed explanation of this, please refer to the experimental examples described below.

[0089] Unless otherwise defined, the term "surface of the primary particle" used in this application means the outer surface of the primary particle exposed to the outside. Similarly, the term "surface of the secondary particle" used in this application means the outer surface of the secondary particle exposed to the outside. In this case, the "surface of the secondary particle" formed by agglomeration of a plurality of primary particles corresponds to the exposed surface of the primary particle present in the surface portion of the secondary particle.

[0090] In addition, unless otherwise defined, the term "surface portion of a particle" used in the present application means a region relatively closer to the "surface" of a particle, and the term "central portion of a particle" means a region relatively closer to the "center" of a particle than the "surface portion". Thus, the term "surface portion of a primary particle" means a region relatively closer to the "surface" of the primary particle, and the term "central portion of a primary particle" means a region relatively closer to the "center" of the primary particle than the "surface portion". Similarly, the term "surface portion of a secondary particle" means a region relatively closer to the "surface" of the secondary particle, and the term "central portion of a secondary particle" means a region relatively closer to the "center" of the secondary particle than the "surface portion".

[0091] In this case, the region within any particle excluding the "surface portion of the particle" can be defined as the "center portion of the particle."

[0092] For example, when the radius of the primary particle is r, a region that is 0 to 0.5r away from the surface of the primary particle can be defined as the surface portion of the primary particle, and a region that is 0 to 0.5r away from the center of the primary particle can be defined as the center portion of the primary particle. If the radius of the primary particle is 0.5 μm, the surface portion of the primary particle can be defined as a region that is 0 to 0.25 μm away from the surface of the primary particle, and the center portion of the primary particle can be defined as a region that is 0 to 0.25 μm away from the center of the primary particle.

[0093] Furthermore, if necessary, when the radius of the primary particle is referred to as r, a region that is 0 to 0.1r or 0 to 0.2r away from the surface of the primary particle can be defined as the surface portion of the primary particle, and a region that is 0 to 0.2r or 0 to 0.5r away from the center of the primary particle can be defined as the central portion of the primary particle.

[0094] Similarly, when the radius of the secondary particle is r, the region that is 0 to 0.5r away from the surface of the secondary particle can be defined as the surface portion of the secondary particle, and the region that is 0 to 0.5r away from the center of the secondary particle can be defined as the center portion of the secondary particle. If the radius of the secondary particle is 2.0 μm, the surface portion of the secondary particle can be defined as the region that is 0 to 1.0 μm away from the surface of the secondary particle, and the center portion of the secondary particle can be defined as the region that is 0 to 1.0 μm away from the center of the secondary particle.

[0095] Furthermore, if necessary, when the radius of the secondary particle is referred to as r, a region that is 0 to 0.1r or 0 to 0.2r away from the surface of the secondary particle can be defined as the surface portion of the secondary particle, and a region that is 0 to 0.2r or 0 to 0.5r away from the center of the secondary particle can be defined as the center portion of the secondary particle.

[0096] The lithium manganese-based oxide defined herein may be a lithium-excess lithium manganese-based oxide represented by the following Chemical Formula 1. The composition represented by the following Chemical Formula 1 may represent an average composition reflecting the composition of a barrier layer present on at least a portion of the surface of the lithium manganese-based oxide.

[0097] [Chemical formula 1] Li (Li a M1 x M2 y )O 2-b X b where M1 is at least one selected from Ni and Mn; M2 is at least one selected from Ni, Mn, Co, Al, P, Nb, B, Ti, Zr, Ba, K, Mo, Si, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, V, Ta, Sn, Hf, Ce, Gd, and Nd, and M2 does not overlap with M1; X is a halogen capable of substituting at least a part of the oxygen present in the lithium manganese oxide, <a≦0.7、0<b≦0.1、0<x≦1、0≦y<1、0<x+y≦1である。

[0098] The types of halogen that can be used as X can be referred to the periodic table, and F, Cl, Br, and / or I can be used, preferably F can be used.

[0099] In addition, the lithium-excess lithium manganese oxide represented by Chemical Formula 1 may further contain a spinel phase in addition to the phase belonging to the C2 / m space group and the phase belonging to the R3-m space group.

[0100] In other embodiments, the lithium manganese oxide may be represented by the following Chemical Formula 1-1. The composition represented by the following Chemical Formula 1-1 can represent an average composition reflecting the composition of the barrier layer present in at least a part of the surface of the lithium manganese oxide.

[0101] [Chemical Formula 1-1] rLi2MnO 3-b″ X′ b″ ·(1-r)Li a′ M1 x′ M2 y′ O 2-b′ X b′ Here, M1 is at least one selected from Ni and Mn, M2 is at least one selected from Ni, Mn, Co, Al, P, Nb, B, Ti, Zr, Ba, K, Mo, Si, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, V, Ta, Sn, Hf, Ce, Gd, and Nd, and M2 does not overlap with M1, X and X′ are halogens that can substitute at least a part of the oxygen present in the lithium manganese oxide, 0 < r ≦ 0.7, 0 < a′ ≦ 1, 0 ≦ b′ ≦ 0.1, 0 ≦ b″ ≦ 0.1, 0 < x′ ≦ 1, 0 ≦ y′ < 1, and 0 < x′ + y′ ≦ 1, provided that b′ and b″ are not both 0 at the same time.

[0102] The types of halogen usable as X and X' refer to the periodic table, and F, Cl, Br and / or I can be used, with F being preferred.

[0103] In the chemical formula 1 and the chemical formula 1-1, when M1 is Ni, M2 may contain Mn, and when M1 is Mn, M2 may contain Ni. Also, when M1 is Ni and Mn, M2 may be absent, or, if present, may be another element other than Ni and Mn.

[0104] That is, when M1 is Ni, M2 may include at least one selected from Co, Al, P, Nb, B, Ti, Zr, Ba, K, Mo, Si, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, V, Ta, Sn, Hf, Ce, Gd, and Nd (preferably, at least one selected from Co, Al, P, Nb, B, Ti, Zr, Ba, K, Mo, Si, and W, more preferably, at least one selected from Co, P, B, Ti, Zr, Si, and W, more preferably, at least one selected from P, B, and Si) and Mn.

[0105] When M1 is Mn, M2 may include at least one selected from Co, Al, P, Nb, B, Ti, Zr, Ba, K, Mo, Si, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, V, Ta, Sn, Hf, Ce, Gd, and Nd (preferably, at least one selected from Co, Al, P, Nb, B, Ti, Zr, Ba, K, Mo, Si, and W, more preferably, at least one selected from Co, P, B, Ti, Zr, Si, and W, more preferably, at least one selected from P, B, and Si) and Ni.

[0106] When M1 is Ni and Mn, M2 may include at least one selected from Co, Al, P, Nb, B, Ti, Zr, Ba, K, Mo, Si, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, V, Ta, Sn, Hf, Ce, Gd and Nd, preferably at least one selected from Co, Al, P, Nb, B, Ti, Zr, Ba, K, Mo, Si and W, more preferably at least one selected from Co, P, B, Ti, Zr, Si and W, more preferably at least one selected from P, B and Si.

[0107] As described above, when inducing crystal growth or particle growth of the primary particles constituting the lithium manganese-based oxide, in the case of doping with a halogen, preferably, at least a portion of oxygen present in the lithium manganese-based oxide may be substituted with a halogen.

[0108] When a heat treatment is performed at a relatively high temperature without halogen doping in order to induce crystal growth or particle growth of the primary particles constituting the lithium manganese-based oxide, the crystal structure of the primary particles may be damaged, resulting in early deterioration of the positive electrode active material, although the crystal growth or particle growth of the primary particles is possible.

[0109] In addition, in the case of the over-firing method, the primary particles grow in a non-directional manner, whereas when a halogen is doped during the growth of the primary particles, the primary particles grow in a partially directional manner, thereby mitigating the decrease in the diffusibility of lithium ions due to the growth of the primary particles. In particular, it is preferable to use fluorine as the halogen and fluorine as an anion dopant for the growth of the primary particles, from the viewpoint of inducing crystal growth or particle growth of the primary particles in a selective direction within a range that mitigates the decrease in the diffusibility of lithium ions mediated by the primary particles.

[0110] For fluorine doping of the primary particles, at least one anion dopant selected from LiF, MgF2, HF, F2, XeF2, TbF4, CeF4, CoF3, AgF2, MoF3, AgF, CuF2, FeF3, CuF, VF3, CrF3, ZrF4, BaF2, CaF2, AlF3, NH4F, CeF3 and CsF, preferably at least one anion dopant selected from LiF and MgF2, can be used.

[0111] The content of fluorine doped in the primary particles can be predicted from the content of fluorine in the lithium manganese-based oxide represented by Formula 1 (i.e., the values ​​of b' and b" in Formula 1). In addition, when b' and b" in Formula 1 are not both 0, b'+b" may be 0.2 or less, preferably 0.1 or less.

[0112] The lithium manganese-based oxide represented by Formula 1 or Formula 1-1 may selectively contain cobalt. When the lithium manganese-based oxide contains cobalt, the mole fraction of the cobalt relative to the moles of all metal elements in the lithium manganese-based oxide may be 20% or less, preferably 15% or less, and more preferably 10% or less. In other cases, the lithium manganese-based oxide represented by Formula 1 may have a cobalt-free composition that does not contain cobalt.

[0113] The Li / Metal molar ratio measured from the lithium manganese-based oxide represented by Chemical Formula 1 or Chemical Formula 1-1 may be greater than 1, preferably 1.1 to 1.7, and more preferably 1.2 to 1.6. When the Li / Metal molar ratio measured from the lithium manganese-based oxide has a value greater than 1, it is possible to form a lithium-excess lithium manganese-based oxide. In addition, in order for the lithium manganese-based oxide to appropriately form a solid solution or a composite solid solution of a phase belonging to the C2 / m space group and a phase belonging to the R3-m space group and to exhibit high capacity under a high voltage operating environment, the Li / Metal molar ratio of the lithium manganese-based oxide is preferably 1.2 to 1.6.

[0114] In order to properly form a solid solution in which a phase belonging to the C2 / m space group and a phase belonging to the R3-m space group are dissolved or combined, the content of manganese in all metal elements excluding lithium present in the lithium manganese-based oxide represented by Chemical Formula 1 or Chemical Formula 1-1 is preferably 50 mol % or more.

[0115] In order for the lithium manganese-based oxide to have the OLO characteristic of exhibiting high capacity under a high voltage operating environment, the manganese content of all metal elements excluding lithium present in the lithium manganese-based oxide is preferably 50 mol% or more and less than 80 mol%, more preferably 55 mol% to 75 mol%. When the manganese content in the lithium manganese-based oxide exceeds 80 mol%, a phase transition may occur due to the movement of transition metals (especially manganese) in the lithium manganese-based oxide during formation and / or operation of the lithium secondary battery. Such a phase transition forms a spinel phase, and the spinel phase acting as an impurity in the lithium manganese-based oxide may induce a decrease in charge / discharge capacity or a voltage decay during the charge / discharge cycle of the lithium secondary battery.

[0116] In order to properly form a solid solution in which a phase belonging to the C2 / m space group and a phase belonging to the R3-m space group are dissolved or combined, the content of nickel in all metal elements excluding lithium present in the lithium manganese-based oxide represented by Chemical Formula 1 or Chemical Formula 1-1 is preferably less than 50 mol%.

[0117] When the nickel content in the lithium manganese-based oxide is 50 mol % or more, the C2 / m phase is difficult to form sufficiently, or the phase belonging to the C2 / m space group and the phase belonging to the R3-m space group do not form a sufficient solid solution, which may cause phase separation during formation and / or operation of the lithium secondary battery.

[0118] In general, commercially available ternary lithium composite oxides having a nickel-cobalt-manganese (NCM) or nickel-cobalt-aluminum (NCA) composition exist in a single phase belonging to the R3-m space group.

[0119] Meanwhile, the lithium-rich lithium manganese oxide represented by the formula 1 or the formula 1-1 is rLi2MnO 3-b″ X′ b″ The oxides of the phase belonging to the C2 / m space group represented by the formula (hereinafter referred to as the "C2 / m phase") and (1-r)Li a′ M1 x′ M2 y′ O 2-b′ X b′ The lithium manganese-based oxide exists as a composite oxide in which an oxide of the C2 / m phase and an oxide of the R3-m phase form a solid solution or are combined with each other. For example, the lithium manganese-based oxide may exist in a state in which an oxide of the C2 / m phase and an oxide of the R3-m phase form a solid solution.

[0120] In this case, a complex oxide in which a phase belonging to the C2 / m space group and a phase belonging to the R3-m space group are simply physically and / or chemically bonded or attached does not fall under the category of a solid solution as defined in this application.

[0121] For example, a composite oxide having a phase belonging to the C2 / m space group, in which a metal oxide having a phase belonging to the C2 / m space group and a metal oxide having a phase belonging to the R3-m space group are mixed and the surface of the composite oxide is coated with a metal oxide having a phase belonging to the R3-m space group, does not fall under the category of a solid solution as defined in the present application.

[0122] In the lithium manganese-based oxide represented by the formula 1-1, when r exceeds 0.7, the lithium manganese-based oxide is an oxide of C2 / m phase, Li2MnO 3-b″ X′ b″ In other words, in order to sufficiently activate the C2 / m phase oxide, which has a relatively high resistance in the lithium manganese-based oxide, and improve the surface kinetics, it is preferable that the R3-m phase oxide is present at a certain ratio or more.

[0123] Furthermore, when the surface of the lithium manganese-based oxide defined in the present application, i.e., at least a portion of the surface of the primary particles and / or the secondary particles, is covered with a barrier layer, it is possible to suppress or mitigate the elution of a transition metal from the lithium manganese-based oxide.

[0124] The barrier layer can suppress or mitigate the elution of the transition metal from the primary particles and / or the secondary particles by covering at least a part of the surface of the primary particles and / or the secondary particles. In particular, the barrier layer can prevent a side reaction between the surface of the secondary particles and the electrolyte by covering the surface of the secondary particles.

[0125] When the barrier layer covers a part of the surface of the secondary particle, the barrier layer may be present in an island form. That is, even if the barrier layer covers at least a part of the surface of the secondary particle in an island form, the elution of the transition metal through the area covered by the barrier layer can be suppressed or reduced. Therefore, the barrier layer being present on the surface of the secondary particle must be distinguished from the lithium manganese-based oxide and a different oxide being simply attached to the surface of the secondary particle in a dispersed state.

[0126] In addition, a grain boundary may be defined between adjacent primary particles in the secondary particle, and the barrier layer may be present in a state of being diffused from a surface portion of the secondary particle toward a center portion of the secondary particle along the grain boundary. As the barrier layer diffuses toward the center portion of the secondary particle, the elements mainly contained in the barrier layer may show a concentration gradient that decreases from the surface portion of the secondary particle toward the center portion of the secondary particle.

[0127] The barrier layer forms a gradient from the surface portion of the secondary particle toward the center portion of the secondary particle, thereby effectively suppressing or mitigating the elution of transition metal mainly at the surface portion of the secondary particle.

[0128] A portion of the elements primarily contained in the barrier layer may be doped into the primary particles and / or the secondary particles.

[0129] The average thickness of the barrier layer covering the surfaces of the secondary particles is preferably 0.1 nm to 1 μm.

[0130] If the average thickness of the barrier layer covering the secondary particles is less than 0.1 nm, it may be difficult to sufficiently prevent the transition metal from eluting from the secondary particles, whereas if the average thickness of the barrier layer covering the secondary particles is more than 1 μm, the surface kinetics of the secondary particles may decrease, or the electrical conductivity of the secondary particles may decrease.

[0131] The barrier layer covers at least a portion of the surface of the primary particles, thereby suppressing or reducing the elution of the transition metal from the primary particles to the outside. In addition, the barrier layer covers the surface of the primary particles, thereby preventing a side reaction between the surface of the primary particles and the electrolyte. In this case, the barrier layer covers the surface of the primary particles present on the surface portion of the secondary particles, thereby covering at least a portion of the surface of the secondary particles. When the barrier layer covers a portion of the surface of the primary particles and / or the secondary particles, the barrier layer may be present in an island form.

[0132] The average thickness of the barrier layer covering the surfaces of the primary particles is preferably 0.1 nm to 1 μm.

[0133] If the average thickness of the barrier layer covering the primary particles is less than 0.1 nm, it may be difficult to sufficiently prevent the transition metal from eluting from the primary particles, whereas if the average thickness of the barrier layer covering the primary particles is more than 1 μm, the surface kinetics of the primary particles may decrease, or the electrical conductivity of the secondary particles may decrease.

[0134] In one embodiment, the barrier layer may include a first oxide represented by Formula 2 below:

[0135] [Chemical formula 2] Li c B d M3 e O f Here, M3 is at least one selected from Ni, Mn, Co, Al, Nb, Ti, Zr, Ba, K, Mo, Si, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, V, Ta, Sn, Hf, Ce, Gd, and Nd, and 0≦c≦8, 0 <d≦8、0≦e≦8、2≦f≦13である。

[0136] When the first oxide represented by Formula 2 is a borate-based compound or a lithium borate (LBO)-based compound, non-limiting examples of the first oxide include B2O3, Li2O-B2O3, Li3BO3, Li2B4O7, Li2B2O7, and Li2BO. 13 The first oxide may have a composition in which the borate-based compound or the lithium borate-based compound is selectively doped with a different element M3.

[0137] In this case, a gradient may be formed in which the concentration of at least one selected from B and M3 decreases from the barrier layer toward the core of the lithium manganese-based oxide due to diffusion and / or doping of the first oxide contained in the barrier layer.

[0138] Such a concentration gradient serves as a path for the movement of lithium ions within and between the primary particles, thereby improving the transport / diffusion efficiency of the lithium ions via the primary particles.

[0139] In another embodiment, the barrier layer may further include a second oxide represented by the following Formula 3:

[0140] [Chemical formula 3] Li g M4 h O i Here, M4 is at least one selected from Ni, Mn, Co, Al, Nb, Ti, Zr, Ba, K, Mo, Si, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, V, Ta, Sn, Hf, Ce, Gd, and Nd, and 0≦g≦8, 0≦h≦8, 2≦i≦13, except when g and h are simultaneously 0.

[0141] Non-limiting examples of the second oxide represented by Formula 3 include Li g Zr h O i , Li gTi h O i 、Li g Ni h O i 、Li g Nb h O i 、Li g Co h O i 、Li g Si h O i 、Li g Al h O i 、Co h O i 、Mn h O i 、Al h O i 、Si h O i 、Zr h O i 、Ti h O i and so on.

[0142] At this time, a gradient in which the concentration of M4 decreases from the barrier layer toward the core of the lithium manganese oxide may be formed due to diffusion and / or doping of the second oxide contained in the barrier layer.

[0143] In still another embodiment, the barrier layer may include a third oxide represented by the following Chemical Formula 4.

[0144] [Chemical Formula 4] Li j M5 k (P l O m ) n Here, M5 is at least one selected from Ni, Mn, Co, Al, Nb, B, Ti, Zr, Ba, K, Mo, Si, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, V, Ta, Sn, Hf, Ce, Gd, and Nd; 0 ≦ j ≦ 10, 0 ≦ k ≦ 8, 0 < l ≦ 4, 0 < m ≦ 10, 0 < n ≦ 13; and the case where j and k are simultaneously 0 is excluded.

[0145] Non-limiting examples of the third oxide represented by Formula 4 include Li j (P l O m ) n , Li j Al k (P l O m ) n , Al k (P l O m ) n , (P l O m ) n , Li j Mn k (P l O m ) n , Mn k (P l O m ) n , Li j Ni k (P l O m ) n , Ni k (P l O m ) n etc.

[0146] In this case, a gradient may be formed in which the concentration of at least one selected from M5 and P decreases from the barrier layer toward the core of the lithium manganese-based oxide due to diffusion and / or doping of the third oxide contained in the barrier layer.

[0147] It is known that the decrease in charge / discharge capacity or voltage decay during charge / discharge cycles of lithium secondary batteries using OLO is induced by a phase transition caused by the movement of transition metals in lithium manganese oxide. For example, when a phase transition is induced by the movement of transition metals in an unintended direction in a lithium manganese oxide with a layered crystal structure, a spinel or similar crystal structure may be formed entirely and / or partially in the lithium manganese oxide.

[0148] However, unlike the spinel phase formed by phase transition due to migration of transition metals in the lithium manganese-based oxide, when a spinel phase is formed on the surface of the primary particles and / or the secondary particles while inducing crystal growth or particle growth of the primary particles constituting the lithium manganese-based oxide, such a spinel phase not only contributes to surface stabilization of the lithium manganese-based oxide but also serves as a two-dimensional and / or three-dimensional path for diffusion of lithium ions within the lithium manganese-based oxide. The spinel phase present on the surface of the primary particles and / or the secondary particles may be represented by Chemical Formula 4.

[0149] As a result, by making the spinel phase compound present in the barrier layer, which exists to suppress the elution of transition metals from the primary particles and / or the secondary particles, the lithium manganese-based oxide can exhibit an appropriate level of electrical conductivity even if the surfaces of the primary particles and / or the secondary particles are covered with the barrier layer.

[0150] If necessary, the barrier layer may contain at least two oxides selected from a first oxide, a second oxide, and a third oxide in order to effectively suppress or mitigate the elution of transition metals from the lithium manganese oxide and at the same time improve the surface kinetics of the lithium manganese oxide. The barrier layer preferably contains at least one oxide selected from the first oxide represented by the above chemical formula 2, the second oxide represented by the above chemical formula 3, and the third oxide represented by the above chemical formula 4.

[0151] In addition, the content of the main constituent element of the barrier layer calculated based on all metal elements excluding lithium present in the lithium manganese oxide is preferably more than 0.1 mol% and less than 5 mol%. Here, when the first oxide is present in the barrier layer, the main constituent element of the barrier layer is boron (B) and M3, when the second oxide is present in the barrier layer, the main constituent element of the barrier layer is M4, and when the third oxide is present in the barrier layer, the main constituent element of the barrier layer is M5. In addition, when any combination of the first oxide to the third oxide is present in the barrier layer, the main constituent element of the barrier layer is selected from boron (B), M3, M4, and M5.

[0152] The content of the main constituent elements of the barrier layer being less than 0.1 mol% means that the barrier layer for suppressing or mitigating the elution of the transition metal is insufficiently formed on the surface of the lithium manganese-based oxide, which makes it difficult to effectively prevent the accelerated deterioration of the life span of the lithium secondary battery caused by the precipitation of impurities in the positive and / or negative electrodes due to the transition metal eluted from the lithium manganese-based oxide.

[0153] On the other hand, if the content of the main constituent element of the barrier layer is 5 mol % or more, the surface kinetics of the lithium manganese-based oxide may be decreased, and therefore the electrochemical properties may be deteriorated as compared to the case where the main constituent element of the barrier layer is present in an appropriate content.

[0154] In order to effectively suppress or reduce the elution of transition metals from the surface of the lithium manganese-based oxide without decreasing the surface kinetics of the lithium manganese-based oxide, the content of the main constituent elements of the barrier layer calculated based on the total metal elements excluding lithium present in the lithium manganese-based oxide is more preferably 1±0.1 mol% or more and 3±0.1 mol% or less.

[0155] Lithium secondary battery According to another aspect of the present invention, there is provided a positive electrode including a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector, wherein the positive electrode active material layer may include the lithium manganese-based oxide according to the various embodiments of the present invention as a positive electrode active material.

[0156] Therefore, a specific description of the lithium manganese oxide will be omitted, and only the remaining components not described above will be described below. For convenience, the lithium manganese oxide described above will be referred to as the positive electrode active material.

[0157] The positive electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has conductivity, and may be, for example, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. The positive electrode current collector may usually have a thickness of 3 to 500 μm, and fine irregularities may be formed on the surface of the current collector to increase the adhesive strength of the positive electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0158] The positive electrode active material layer may be prepared by coating a positive electrode slurry composition containing the positive electrode active material, a conductive material, and optionally a binder, on the positive electrode current collector.

[0159] At this time, the positive electrode active material may be included in a content of 80 wt% to 99 wt%, more specifically, 85 wt% to 98.5 wt%, based on the total weight of the positive electrode active material layer, and excellent capacity characteristics can be exhibited when the content is within this range, but is not necessarily limited thereto.

[0160] The conductive material is used to impart conductivity to the electrode, and can be used without any particular limitation as long as it has electronic conductivity without causing chemical changes in the battery that is constructed. Specific examples include graphite such as natural graphite and artificial graphite, carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, carbon-based materials such as carbon fibers, metal powders or metal fibers such as copper, nickel, aluminum, and silver, conductive whiskers such as zinc oxide and potassium titanate, conductive metal oxides such as titanium oxide, and conductive polymers such as polyphenylene derivatives, and the like, and one or more of these may be used alone or in combination. The conductive material may be contained in an amount of 0.1 wt% to 15 wt% based on the total weight of the positive electrode active material layer.

[0161] The binder serves to improve the adhesion between the positive electrode active material particles and the adhesive strength between the positive electrode active material and the current collector. Specific examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated-EPDM, styrene-butadiene rubber (SBR), fluororubber, and various copolymers thereof, and among these, one type alone or a mixture of two or more types may be used. The binder may be included in an amount of 0.1 to 15 wt% based on the total weight of the positive electrode active material layer.

[0162] The positive electrode may be manufactured by a typical method for manufacturing a positive electrode, except for using the positive electrode active material. Specifically, the positive electrode may be manufactured by dissolving or dispersing the positive electrode active material and, optionally, a binder and a conductive material in a solvent to prepare a positive electrode slurry composition, which is then coated on a positive electrode current collector, followed by drying and rolling.

[0163] The solvent may be a solvent commonly used in the art, such as dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone, or water, and one or more of these may be used alone or in combination. The amount of the solvent used is sufficient to dissolve or disperse the positive electrode active material, conductive material, and binder, and to provide a viscosity that allows excellent thickness uniformity when applied to manufacture a positive electrode, taking into consideration the coating thickness of the slurry and the production yield.

[0164] In another embodiment, the positive electrode may be manufactured by casting the positive electrode slurry composition on a separate support, peeling the positive electrode slurry composition from the support, and laminating the resulting film on a positive electrode current collector.

[0165] According to yet another aspect of the present invention, there may be provided an electrochemical device including the above-mentioned positive electrode. The electrochemical device may be, for example, a battery or a capacitor, and more specifically, a lithium secondary battery.

[0166] Specifically, the lithium secondary battery may include a positive electrode, a negative electrode facing the positive electrode, and a separator and an electrolyte interposed between the positive electrode and the negative electrode. Here, since the positive electrode is as described above, a detailed description thereof will be omitted for convenience, and only the remaining components not described above will be described in detail below.

[0167] The lithium secondary battery may optionally further include a battery container that houses an electrode assembly of the positive electrode, the negative electrode, and the separator, and a sealing member that seals the battery container.

[0168] The negative electrode may include a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector.

[0169] The negative electrode current collector is not particularly limited as long as it has high conductivity without inducing chemical changes in the battery, and may be, for example, copper, stainless steel, aluminum, nickel, titanium, baked carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, or aluminum-cadmium alloy. The negative electrode current collector may generally have a thickness of 3 μm to 500 μm, and like the positive electrode current collector, the surface of the current collector may be formed with fine irregularities to strengthen the binding force of the negative electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, or nonwoven fabric.

[0170] The negative electrode active material layer may be prepared by coating a negative electrode slurry composition containing the negative electrode active material, a conductive material, and optionally a binder, on the negative electrode current collector.

[0171] The negative electrode active material may be a compound capable of reversible intercalation and deintercalation of lithium. Specific examples of the negative electrode active material include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon, metallic compounds capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, and Al alloys, and SiO β(0<β<2), metal oxides capable of doping and dedoping lithium, such as SnO2, vanadium oxide, and lithium vanadium oxide, or composites containing the metallic compounds and carbonaceous materials, such as Si-C composites and Sn-C composites, may be used. A metallic lithium thin film may be used as the negative electrode active material. Low-crystalline carbon and high-crystalline carbon may both be used as the carbon material. Representative examples of low crystalline carbon include soft carbon and hard carbon, and representative examples of high crystalline carbon include amorphous, plate-like, flake-like, spherical or fibrous natural graphite or artificial graphite, kish graphite, pyrolytic carbon, mesophase pitch based carbon fiber, carbon microbeads, mesophase pitches, and high-temperature fired carbon such as petroleum or coal tar pitch derived cokes.

[0172] The negative electrode active material may be included in an amount of 80 wt % to 99 wt % based on the total weight of the negative electrode active material layer.

[0173] The binder is a component that aids in bonding between the conductive material, the active material, and the current collector, and may be added in an amount of 0.1 wt% to 10 wt% based on the total weight of the negative electrode active material layer. Examples of such binders include polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber, nitrile-butadiene rubber, fluororubber, and various copolymers thereof.

[0174] The conductive material may be added as a component for further improving the conductivity of the negative electrode active material in an amount of 10 wt% or less, preferably 5 wt% or less, based on the total weight of the negative electrode active material layer. Such a conductive material is not particularly limited as long as it has conductivity without inducing a chemical change in the battery, and may be, for example, graphite such as natural graphite or artificial graphite, carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, or thermal black, conductive fibers such as carbon fibers or metal fibers, metal powders such as carbon fluoride, aluminum, or nickel powder, conductive whiskers such as zinc oxide or potassium titanate, conductive metal oxides such as titanium oxide, or conductive materials such as polyphenylene derivatives.

[0175] In one embodiment, the negative electrode active material layer may be prepared by coating a negative electrode slurry composition prepared by dissolving or dispersing a negative electrode active material, and optionally a binder and a conductive material, in a solvent on a negative electrode current collector and drying the coating. Alternatively, the negative electrode slurry composition may be cast on a separate support, and then peeled off from the support to obtain a film, which may be laminated on the negative electrode current collector.

[0176] In another embodiment, the negative electrode active material layer may be manufactured by coating a negative electrode slurry composition prepared by dissolving or dispersing a negative electrode active material, and optionally a binder and a conductive material, in a solvent on a negative electrode current collector and drying the coating, or by casting the negative electrode slurry composition on a separate support and peeling the composition from the support to obtain a film, which may be laminated on the negative electrode current collector.

[0177] Meanwhile, in the lithium secondary battery, the separator separates the negative electrode and the positive electrode to provide a path for lithium ions to move. Any separator that is generally used as a separator in a lithium secondary battery may be used without any particular limitation. In particular, it is preferable that the separator has low resistance to ion movement of the electrolyte and has excellent electrolyte humidification ability. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof may be used. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of high-melting point glass fiber, polyethylene terephthalate fiber, etc. may be used. In addition, in order to ensure heat resistance or mechanical strength, a coated separator containing a ceramic component or a polymer material may be used, and may be selectively used as a single layer or multilayer structure.

[0178] In addition, examples of the electrolyte used in the present invention include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in the production of lithium secondary batteries, but are not limited to these.

[0179] Specifically, the electrolyte may include an organic solvent and a lithium salt.

[0180] The organic solvent may be used without any particular limitation as long as it serves as a medium through which ions involved in the electrochemical reaction of the battery can move. Specifically, the organic solvent may be an ester solvent such as methyl acetate, ethyl acetate, γ-butyrolactone, or ε-caprolactone, an ether solvent such as dibutyl ether or tetrahydrofuran, a ketone solvent such as cyclohexanone, an aromatic hydrocarbon solvent such as benzene or fluorobenzene, dimethylcarbonate (DMC), diethylcarbonate (DEC), methylethylcarbonate (MEC), ethylmethylcarbonate (EMC), ethylene carbonate (EC), or propylene carbonate (propylene carbonate). Examples of the solvents that may be used include carbonate-based solvents such as ethylene carbonate (PC), alcohol-based solvents such as ethyl alcohol and isopropyl alcohol, nitriles such as R-CN (R is a straight-chain, branched or cyclic hydrocarbon group having 2 to 20 carbon atoms, which may contain a double bond aromatic ring or an ether bond), amides such as dimethylformamide, dioxolanes such as 1,3-dioxolane, and sulfolanes. Among these, carbonate-based solvents are preferred, and a mixture of a cyclic carbonate (e.g., ethylene carbonate or propylene carbonate) having high ionic conductivity and high dielectric constant that can improve the charge / discharge performance of a battery and a low-viscosity linear carbonate compound (e.g., ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate) is more preferred. In this case, the performance of the electrolyte may be excellent if the cyclic carbonate and the chain carbonate are mixed at a volume ratio of about 1:1 to about 1:9.

[0181] The lithium salt may be used without any particular limitation as long as it is a compound capable of providing lithium ions used in a lithium secondary battery. Specifically, the lithium salt may be LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3), LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, or LiB(C2O4)2. The concentration of the lithium salt is preferably within the range of 0.1 to 2.0M. When the concentration of the lithium salt is within the above range, the electrolyte has appropriate conductivity and viscosity, so that excellent electrolyte performance can be exhibited and lithium ions can be effectively transferred.

[0182] When the electrolyte used in the present application is a solid electrolyte, for example, a solid inorganic electrolyte such as a sulfide-based solid electrolyte, an oxide-based solid electrolyte, a nitride-based solid electrolyte, or a halide-based solid electrolyte may be used, and preferably, a sulfide-based solid electrolyte may be used.

[0183] As the material of the sulfide-based solid electrolyte, a solid electrolyte containing Li, an X element (wherein X is at least one selected from P, As, Sb, Si, Ge, Sn, B, Al, Ga, and In), and S may be used. Examples of the sulfide-based solid electrolyte material include Li2S-P2S5, Li2S-P2S-LiX (wherein X is a halogen element such as I or Cl), Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, Li2S-P2S5-ZmSn (wherein m and n are integers and Z is Ge, Zn or Ga), Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li p MO q(where p, q are integers and M is P, Si, Ge, B, Al, Ga or In).

[0184] The solid electrolyte, preferably the sulfide-based solid electrolyte, may be amorphous or crystalline, or may be in a mixed amorphous and crystalline state.

[0185] The oxide-based solid electrolyte material is Li7La3Zr2O 12 , Li 7-x La3Zr 1-x Nb x O 12 , Li 7-3x La3Zr2Al x O 12 , Li 3x La 2 / 3-x TiO3, Li 1+x Al x Ti 2-x (PO4)3, Li 1+x Al x Ge 2-x (PO4)3, Li3PO4, Li 3+x PO 4-x N x (LiPON), Li 2+2x Zinc 1-x Examples include GeO4 (LISICON).

[0186] The solid electrolyte may be disposed as a separate layer (solid electrolyte layer) between the positive electrode and the negative electrode. The solid electrolyte may be partially included in the positive electrode active material layer of the positive electrode, independent of the solid electrolyte layer, or the solid electrolyte may be partially included in the negative electrode active material layer of the negative electrode, independent of the solid electrolyte layer.

[0187] In addition to the electrolyte components, the electrolyte may further contain one or more additives such as haloalkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum trichloride, for the purpose of improving the life characteristics of the battery, suppressing the decrease in battery capacity, improving the discharge capacity of the battery, etc. In this case, the additives may be contained in an amount of 0.1 to 5 wt% based on the total weight of the electrolyte.

[0188] As described above, the lithium secondary battery including the positive electrode active material according to the present invention stably exhibits excellent discharge capacity, output characteristics and life characteristics, and is therefore useful in the fields of portable devices such as mobile phones, notebook computers, and digital cameras, and electric vehicles such as hybrid electric vehicles (HEVs).

[0189] The external shape of the lithium secondary battery according to the present invention is not particularly limited, and may be a cylindrical shape using a can, a square shape, a pouch shape, a coin shape, etc. Furthermore, the lithium secondary battery can be used not only as a battery cell used as a power source for a small device, but also preferably as a unit battery for a medium- to large-sized battery module including a plurality of battery cells.

[0190] According to yet another aspect of the present invention, there may be provided a battery module including the lithium secondary battery as a unit cell and / or a battery pack including the same.

[0191] The battery module or the battery pack can be used as a power source for one or more medium- to large-sized devices, such as a power tool, an electric vehicle (Electric Vehicle (EV), a hybrid electric vehicle, and a plug-in hybrid electric vehicle (PHEV), or a power storage system.

[0192] The present invention will be described in more detail below with reference to examples. However, these examples are for the purpose of illustrating the present invention, and the scope of the present invention is not to be construed as being limited by these examples.

[0193] Production Example 1. Production of positive electrode active material Example 1 (a) Preparation of precursor The reactor was charged with an aqueous solution of NiSO4·6H2O and MnSO4·H2O mixed in a molar ratio of 40:60, NaOH, and NH4OH while stirring. The temperature inside the reactor was maintained at 45°C, and the precursor synthesis reaction was carried out while feeding N2 gas into the reactor. After the reaction was completed, the reactor was washed and dehydrated, and the Ni 0.4 Mn 0.6 A hydroxide precursor with the composition (OH)2 was obtained.

[0194] (b) First heat treatment The temperature of the calcination furnace in an O2 atmosphere was increased at a rate of 2°C / min, and then the temperature was kept at 550°C. The hydroxide precursor obtained in the above step (a) was heat-treated for 5 hours, and then the furnace was cooled to obtain a precursor in an oxide state.

[0195] (c) Second heat treatment The oxide precursor obtained in the step (b), a lithium source material LiOH (Li / Metal molar ratio=1.25), and LiF weighed out so that the fluorine (F) content based on metal elements excluding lithium in the precursor was 1.0 mol % were mixed to prepare a mixture. Next, the temperature of a sintering furnace in an O2 atmosphere was increased at a rate of 2°C / min, and the mixture was heat-treated at 900°C for 8 hours, followed by furnace cooling to obtain a lithium-excess lithium manganese oxide.

[0196] (d) Third heat treatment (formation of barrier layer) The lithium manganese oxide obtained in step (c) was mixed with H3BO3 weighed so that the content of boron in the lithium manganese oxide based on metal elements excluding lithium was 1.2 mol%, and the mixture was then heat-treated in a sintering furnace under an O2 atmosphere for 8 hours by increasing the temperature to 300°C at a rate of 4.4°C per minute. The mixture was then classified and crushed to obtain a final product (average particle size 4.0 μm) on which a barrier layer containing a B-containing compound was formed on the surface.

[0197] Example 2 (a) Preparation of precursor The reactor was charged with an aqueous solution of NiSO4·6H2O and MnSO4·H2O mixed in a molar ratio of 40:60, NaOH, and NH4OH while stirring. The temperature inside the reactor was maintained at 45°C, and the precursor synthesis reaction was carried out while feeding N2 gas into the reactor. After the reaction was completed, the reactor was washed and dehydrated, and the Ni 0.4 Mn 0.6 A hydroxide precursor with the composition (OH)2 was obtained.

[0198] (b) First heat treatment The temperature of the calcination furnace in an O2 atmosphere was increased at a rate of 2°C / min, and then the temperature was kept at 550°C. The hydroxide precursor obtained in the above step (a) was heat-treated for 5 hours, and then the furnace was cooled to obtain a precursor in an oxide state.

[0199] (c) Second heat treatment The oxide precursor obtained in the step (b), a lithium source material LiOH (Li / Metal molar ratio=1.25), and LiF weighed out so that the content of fluorine (F) based on metal elements excluding lithium in the precursor was 1.0 mol % were mixed to prepare a mixture. Next, the temperature of a sintering furnace in an O2 atmosphere was increased at a rate of 2°C / min, and the mixture was heat-treated at 900°C for 8 hours, followed by furnace cooling to obtain a lithium-excess lithium manganese oxide.

[0200] (d) Wet pretreatment The lithium manganese oxide obtained in the step (c) and SiO2 weighed out so that the content of Si in the lithium manganese oxide based on metal elements excluding lithium was 1.0 mol% were added to distilled water under stirring, and the mixture was stirred at 40°C for 12 hours to obtain a lithium manganese oxide with SiO2 distributed on the surface.

[0201] (e) Third heat treatment (formation of barrier layer) The lithium manganese oxide obtained in the step (d) was heat-treated in a sintering furnace in an O2 atmosphere at a temperature of 400°C at a rate of 4.4°C per minute for 8 hours, and then classified and crushed to obtain a final product (average particle size 4.0 μm) on the surface of which a barrier layer containing a Si-containing compound was formed.

[0202] Example 3 (a) Preparation of precursor The reactor was charged with an aqueous solution of NiSO4·6H2O and MnSO4·H2O mixed in a molar ratio of 40:60, NaOH, and NH4OH while stirring. The temperature inside the reactor was maintained at 45°C, and the precursor synthesis reaction was carried out while feeding N2 gas into the reactor. After the reaction was completed, the reactor was washed and dehydrated, and the Ni 0.4 Mn 0.6 A hydroxide precursor with the composition (OH)2 was obtained.

[0203] (b) First heat treatment The temperature of the calcination furnace in an O2 atmosphere was increased at a rate of 2°C / min, and then the temperature was kept at 550°C. The hydroxide precursor obtained in the above step (a) was heat-treated for 5 hours, and then the furnace was cooled to obtain a precursor in an oxide state.

[0204] (c) Second heat treatment The oxide precursor obtained in the step (b), a lithium source material LiOH (Li / Metal molar ratio=1.25), and LiF weighed out so that the content of fluorine (F) based on metal elements excluding lithium in the precursor was 1.0 mol % were mixed to prepare a mixture. Next, the temperature of a sintering furnace in an O2 atmosphere was increased at a rate of 2°C / min, and the mixture was heat-treated at 900°C for 8 hours, followed by furnace cooling to obtain a lithium-excess lithium manganese oxide.

[0205] (d) Wet pretreatment The lithium manganese oxide obtained in the step (c) and NH4H2PO4 weighed out so that the content of metal element standard P excluding lithium in the lithium manganese oxide was 3.0 mol % were added to distilled water under stirring, and then the mixture was stirred at 40°C for 12 hours to obtain a lithium manganese oxide with NH4H2PO4 distributed on the surface.

[0206] (e) Third heat treatment (formation of barrier layer) The lithium manganese oxide obtained in the step (d) was heat-treated in a sintering furnace under an O2 atmosphere for 8 hours by increasing the temperature to 400°C at a rate of 4.4°C per minute, and then classified and crushed to obtain a final product (average particle size 4.0 μm) on which a barrier layer containing a P-containing compound was formed on the surface.

[0207] Comparative Example 1 (a) Preparation of precursor The reactor was charged with an aqueous solution of NiSO4·6H2O and MnSO4·H2O mixed in a molar ratio of 40:60, NaOH, and NH4OH while stirring. The temperature inside the reactor was maintained at 45°C, and the precursor synthesis reaction was carried out while feeding N2 gas into the reactor. After the reaction was completed, the reactor was washed and dehydrated, and the Ni 0.4 Mn 0.6 A hydroxide precursor with the composition (OH)2 was obtained.

[0208] (b) First heat treatment The temperature of the calcination furnace in an O2 atmosphere was increased at a rate of 2°C / min, and then the temperature was kept at 550°C. The hydroxide precursor obtained in the above step (a) was heat-treated for 5 hours, and then the furnace was cooled to obtain a precursor in an oxide state.

[0209] (c) Second heat treatment The oxide precursor obtained in the step (b) and LiOH (Li / Metal molar ratio=1.25), which is a lithium source material, were mixed to prepare a mixture. Next, the temperature of a sintering furnace in an O2 atmosphere was increased at a rate of 2°C / min, and the mixture was kept at 900°C for 8 hours. After that, the mixture was cooled in the furnace, classified, and crushed to obtain the final product, a lithium-rich lithium manganese oxide (average particle size 4.0 μm).

[0210] Comparative Example 2 (a) Preparation of precursor The reactor was charged with an aqueous solution of NiSO4·6H2O and MnSO4·H2O mixed in a molar ratio of 40:60, NaOH, and NH4OH while stirring. The temperature inside the reactor was maintained at 45°C, and the precursor synthesis reaction was carried out while feeding N2 gas into the reactor. After the reaction was completed, the reactor was washed and dehydrated, and the Ni 0.4 Mn 0.6 A hydroxide precursor with the composition (OH)2 was obtained.

[0211] (b) First heat treatment The temperature of the calcination furnace in an O2 atmosphere was increased at a rate of 2°C / min, and then the temperature was kept at 550°C. The hydroxide precursor obtained in the above step (a) was heat-treated for 5 hours, and then the furnace was cooled to obtain a precursor in an oxide state.

[0212] (c) Second heat treatment The oxide precursor obtained in the step (b), a lithium source material LiOH (Li / Metal molar ratio=1.25), and LiF weighed out so that the content of fluorine (F) based on metal elements excluding lithium in the precursor was 1.0 mol % were mixed to prepare a mixture. Next, the temperature of a sintering furnace in an O2 atmosphere was increased at a rate of 2°C / min, and the mixture was kept at 900°C for 8 hours. After that, the mixture was cooled in the furnace, classified, and crushed to obtain the final product, a lithium-rich lithium manganese oxide (average particle size 4.0 μm).

[0213] Comparative Example 3 (a) Preparation of precursor The reactor was charged with an aqueous solution of NiSO4·6H2O and MnSO4·H2O mixed in a molar ratio of 40:60, NaOH, and NH4OH while stirring. The temperature inside the reactor was maintained at 45°C, and the precursor synthesis reaction was carried out while feeding N2 gas into the reactor. After the reaction was completed, the reactor was washed and dehydrated, and the Ni 0.4 Mn 0.6 A hydroxide precursor with the composition (OH)2 was obtained.

[0214] (b) First heat treatment The temperature of the calcination furnace in an O2 atmosphere was increased at a rate of 2°C / min, and then the temperature was kept at 550°C. The hydroxide precursor obtained in the above step (a) was heat-treated for 5 hours, and then the furnace was cooled to obtain a precursor in an oxide state.

[0215] (c) Second heat treatment The oxide precursor obtained in the step (b) and LiOH (Li / Metal molar ratio=1.25), which is a lithium source material, were mixed to prepare a mixture. Next, the temperature of a sintering furnace in an O2 atmosphere was increased at a rate of 2°C / min, and the mixture was heat-treated at 900°C for 8 hours, followed by furnace cooling to obtain a lithium-excess lithium manganese oxide.

[0216] (d) Third heat treatment (formation of barrier layer) The lithium manganese oxide obtained in step (c) was mixed with H3BO3 weighed so that the content of boron in the lithium manganese oxide based on metal elements excluding lithium was 1.2 mol%, and then the mixture was heated to 300°C at a rate of 4.4°C per minute in an O2 atmosphere in a sintering furnace for 8 hours. The mixture was then classified and crushed to obtain a final product (average particle size 4.0 μm) on the surface of which a barrier layer containing a B-containing compound was formed.

[0217] Comparative Example 4 (a) Preparation of precursor The reactor was charged with an aqueous solution of NiSO4·6H2O and MnSO4·H2O mixed in a molar ratio of 40:60, NaOH, and NH4OH while stirring. The temperature inside the reactor was maintained at 45°C, and the precursor synthesis reaction was carried out while feeding N2 gas into the reactor. After the reaction was completed, the reactor was washed and dehydrated, and the Ni 0.4 Mn 0.6 A hydroxide precursor with the composition (OH)2 was obtained.

[0218] (b) First heat treatment The temperature of the calcination furnace in an O2 atmosphere was increased at a rate of 2°C / min, and then the temperature was kept at 900°C. The hydroxide precursor obtained in the above step (a) was heat-treated for 5 hours, and then the furnace was cooled to obtain a precursor in an oxide state.

[0219] (c) Second heat treatment The oxide precursor obtained in the step (b) and LiOH (Li / Metal molar ratio=1.25), which is a lithium source material, were mixed to prepare a mixture. Next, the temperature of a sintering furnace in an O2 atmosphere was increased at a rate of 2°C / min, and the mixture was heat-treated at 900°C for 8 hours, followed by furnace cooling to obtain a lithium-excess lithium manganese oxide.

[0220] (d) Third heat treatment (formation of barrier layer) The lithium manganese oxide obtained in step (c) was mixed with H3BO3 weighed so that the content of boron in the lithium manganese oxide based on metal elements excluding lithium was 1.2 mol%, and then the mixture was heated to 300°C at a rate of 4.4°C per minute in an O2 atmosphere in a sintering furnace for 8 hours. The mixture was then classified and crushed to obtain a final product (average particle size 4.0 μm) on the surface of which a barrier layer containing a B-containing compound was formed.

[0221] Comparative Example 5 (a) Preparation of precursor The reactor was charged with an aqueous solution of NiSO4·6H2O and MnSO4·H2O mixed in a molar ratio of 40:60, NaOH, and NH4OH while stirring. The temperature inside the reactor was maintained at 45°C, and the precursor synthesis reaction was carried out while feeding N2 gas into the reactor. After the reaction was completed, the reactor was washed and dehydrated, and the Ni 0.4 Mn 0.6 A hydroxide precursor with the composition (OH)2 was obtained.

[0222] (b) First heat treatment The temperature of the calcination furnace in an O2 atmosphere was increased at a rate of 2°C / min, and then the temperature was kept at 550°C. The hydroxide precursor obtained in the above step (a) was heat-treated for 5 hours, and then the furnace was cooled to obtain a precursor in an oxide state.

[0223] (c) Second heat treatment The oxide precursor obtained in the step (b), a lithium source material LiOH (Li / Metal molar ratio=1.25), and LiF weighed out so that the content of fluorine (F) based on metal elements excluding lithium in the precursor was 1.0 mol % were mixed to prepare a mixture. Next, the temperature of a sintering furnace in an O2 atmosphere was increased at a rate of 2°C / min, and then the mixture was heat-treated at 1,000°C for 8 hours, followed by furnace cooling to obtain a lithium-excess lithium manganese oxide.

[0224] (d) Third heat treatment (formation of barrier layer) The lithium manganese oxide obtained in step (c) was mixed with H3BO3 weighed so that the content of boron in the lithium manganese oxide based on metal elements excluding lithium was 1.2 mol%, and then the mixture was heated to 300°C at a rate of 4.4°C per minute in an O2 atmosphere in a sintering furnace for 8 hours. The mixture was then classified and crushed to obtain a final product (average particle size 4.0 μm) on the surface of which a barrier layer containing a B-containing compound was formed.

[0225] Composition of lithium manganese oxide The composition (molar ratio of each element) of the lithium manganese-based oxide contained in each of the positive electrode active materials prepared in Preparation Example 1 was measured through ICP analysis. The measurement results are shown in Table 1 below.

[0226] [Table 1] *The Li / Metal molar ratio indicates the molar ratio of lithium to all elements excluding lithium in the lithium manganese oxide. *The element content (mol%) is calculated based on all elements other than lithium in the lithium manganese oxide.

[0227] Manufacturing example 2. Manufacturing of lithium secondary battery (half cell) A positive electrode slurry was prepared by dispersing 90 wt% of the positive electrode active material prepared in Preparation Example 1, 4.5 wt% of carbon black, and 5.5 wt% of PVDF binder in N-methyl-2-pyrrolidone (NMP). The positive electrode slurry was uniformly applied to an aluminum thin film having a thickness of 15 μm and dried in a vacuum at 135° C. to prepare a positive electrode for a lithium secondary battery.

[0228] A half cell was fabricated using a lithium foil as a counter electrode for the positive electrode, a porous polyethylene film (Celgard 2300, thickness: 25 μm) as a separator, and an electrolyte of LiPF6 at a concentration of 1.15 M in a solvent of ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate mixed in a volume ratio of 2:4:4.

[0229] Manufacturing example 3. Manufacturing of lithium secondary batteries (full cells) A positive electrode slurry was prepared by dispersing 90 wt% of the positive electrode active material prepared in Preparation Example 1, 4.5 wt% of carbon black, and 5.5 wt% of PVDF binder in N-methyl-2-pyrrolidone (NMP). The positive electrode slurry was uniformly applied to an aluminum thin film having a thickness of 15 μm and dried in a vacuum at 135° C. to prepare a positive electrode for a lithium secondary battery.

[0230] A full cell was fabricated using a graphite electrode as a counter electrode for the positive electrode, a porous polyethylene film (Celgard 2300, thickness: 25 μm) as a separator, and an electrolyte solution containing LiPF6 at a concentration of 1.15 M in a solvent containing ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate in a volume ratio of 2:4:4.

[0231] Experimental Example 1. Image analysis of positive electrode active material Lithium manganese oxide in the form of secondary particles was separated from each of the positive electrode active materials prepared according to Preparation Example 1, and then photographed using a scanning electron microscope to obtain SEM images.

[0232] Next, one of the secondary particles was selected from the SEM image using an Image analyzer program, and 20 primary particles were selected in order of the longest minor axis length from among the primary particles exposed on the surface of the secondary particle, and the major axis length and minor axis length of each primary particle were measured. From these, the minimum minor axis length A of the primary particles, the maximum minor axis length B of the primary particles, the average minor axis length C of the primary particles, and the proportion D of primary particles among the 20 primary particles whose minor axis length is 100 nm or more were calculated.

[0233] In addition, the BET specific surface area E was calculated from the amount of nitrogen gas adsorbed by the lithium manganese oxide at liquid nitrogen temperature (77 K) using a gas adsorption specific surface area measurement device (MicrotaracBEL, BELSORP-miniII).

[0234] The measurement results are shown in Table 2 below.

[0235] [Table 2]

[0236] Comparing the lithium manganese-based oxide contained in the positive electrode active material according to Example 1 (fluorine doping is induced when the oxide precursor is calcined) and Comparative Example 1 (prepared under the same conditions as Example 1 except that fluorine doping is not induced when the oxide precursor is calcined), it can be seen that the minimum minor axis length A of the primary particles constituting the lithium manganese-based oxide according to Example 1, the maximum minor axis length B of the primary particles, and the average minor axis length C of the primary particles are larger than those of Comparative Example 1, and the BET specific surface area E is smaller than that of Comparative Example 1.

[0237] That is, it can be confirmed that, during the calcination of the oxide precursor of the lithium manganese-based oxide, the crystal growth and particle growth of the primary particles are induced and, at the same time, the primary particles are grown by doping the primary particles with a halogen (fluorine), thereby reducing the BET specific surface area.

[0238] Similarly, it can be confirmed that the minimum value A of the short axis length of the primary particles constituting the lithium manganese-based oxide according to Examples 2 and 3, which use a coating source different from that of Example 1, is greater than 75 nm, the maximum value B of the short axis length of the primary particles is less than 500 nm, and the average value C of the short axis length of the primary particles is greater than 130 nm.

[0239] In addition, even if a raw material for fluorine doping is used when calcining the oxide precursor, referring to the result of Comparative Example 5 in which the calcination temperature of the oxide precursor is 1,000°C, it can be seen that the average minor axis length C of the primary particles is greater than 400 nm due to excessive crystal growth or particle growth of the primary particles.

[0240] In addition, referring to the results of Comparative Example 4 in which fluorine doping was not induced during the calcination of the oxide precursor, but the calcination temperature of the hydroxide precursor was increased to 900°C to induce crystal growth and particle growth of primary particles, it can be seen that larger particle growth was induced than in the results of Comparative Example 5 due to the excessively high calcination temperature in the process of converting the hydroxide precursor to the oxide precursor.

[0241] Experimental Example 2: XPS analysis of positive electrode active material The lithium manganese-based oxides selected from the respective positive electrode active materials prepared in Preparation Example 1 were subjected to XPS analysis to measure the contents of the target elements contained in the lithium manganese-based oxides.

[0242] Specifically, the change in the content of the target element from the surface of the lithium manganese-based oxide (secondary particles) to the lithium manganese-based oxide (secondary particles) was measured by increasing the etching time of the surface of the lithium manganese-based oxide using an XPS depth profile analysis method (ion energy 2000 eV, spot size 200 μm).

[0243] The results of the XPS analysis are shown in Table 3 below.

[0244] [Table 3] *The target element content (at%) is calculated based on all elements except lithium in the lithium manganese oxide.

[0245] Referring to the results in Table 3, it can be seen that the content of the target element present on the surface of the lithium manganese-based oxide (secondary particles) according to Examples 1 to 3 is 20 at% or more. The fact that the content of the target element originating from the raw material used in the third heat treatment on the surface of the lithium manganese-based oxide (secondary particles) is 20 at% or more is presumably due to the formation of a barrier layer on the surface of the lithium manganese-based oxide (secondary particles).

[0246] Experimental Example 3: Evaluation of the electrochemical characteristics of a lithium secondary battery (half cell) The lithium secondary battery (half cell) manufactured in Manufacturing Example 2 was subjected to a charge-discharge experiment at 25° C., voltage range of 2.0V to 4.6V, and discharge rate of 0.1C to 5.0C using an electrochemical analyzer (Toyo, Toscat-3100) to measure the initial charge capacity, initial discharge capacity, initial reversible efficiency, and rate capability (rate capability (C-rate)).

[0247] The measurement results are shown in Table 4 below.

[0248] [Table 4]

[0249] Referring to the results in Table 4, it can be seen that the lithium secondary battery using the positive electrode active material including the lithium manganese-based oxide according to Example 1 (which induces fluorine doping when the oxide precursor is calcined) has higher initial charge capacity, initial discharge capacity, initial reversible efficiency, and discharge capacity than the lithium secondary battery using the positive electrode active material including the lithium manganese-based oxide according to Comparative Example 1 or Comparative Example 3 (which does not induce fluorine doping when the oxide precursor is calcined).

[0250] In addition, even though a raw material for fluorine doping was used when calcining the oxide precursor, the result of Comparative Example 5 in which the calcination temperature was 1,000°C shows that the discharge capacity ratio was lower than that of Comparative Examples 1 and 3.

[0251] In the case of Comparative Example 5, it is expected that the rate of discharge capacity was reduced due to thermal damage to the lithium manganese-based oxide caused by an excessively high sintering temperature during the second heat treatment.

[0252] Referring to the results of Comparative Example 4 in which fluorine doping was not induced during calcination of the oxide precursor, but the calcination temperature of the hydroxide precursor was increased to 900°C to induce crystal growth and particle growth of primary particles, it was found that premature degradation of the positive electrode active material occurred due to thermal damage caused by an excessively high calcination temperature during the conversion of the hydroxide precursor to the oxide precursor, resulting in an overall deterioration of the electrochemical properties.

[0253] Experimental Example 4. Evaluation of the electrochemical characteristics of a lithium secondary battery (full cell) The lithium secondary batteries (full cells) manufactured in Manufacturing Example 3 using the positive electrode active materials according to Examples 1 to 3 and Comparative Example 2 were subjected to a formation process of 6 cycles at 25° C., voltage range of 2.0V to 4.6V, and 0.2C / 0.2C using an electrochemical analyzer (Toyo, Toscat-3100), and then charged and discharged 300 times at 25° C., voltage range of 2.0V to 4.6V, and 1C / 1C. The initial (first cycle) discharge capacity and the ratio of the discharge capacity at the 100th cycle, 200th cycle, and 300th cycle to the initial discharge capacity (cycle capacity retention rate; capacity retention) were measured.

[0254] The measurement results are shown in Table 5 below.

[0255] [Table 5]

[0256] Referring to the full cell evaluation results in Table 5, it can be seen that in Comparative Example 2, where a raw material for fluorine doping is used when calcining an oxide precursor, but a barrier layer is not formed on the surface of the lithium manganese-based oxide, the cycle capacity retention rate is rapidly decreased. This result is believed to be due to the fact that the transition metal is eluted from the lithium manganese-based oxide, causing a resistance abnormality phenomenon in the negative electrode, which accelerates the deterioration of the lifespan of the lithium secondary battery.

[0257] Meanwhile, in the case of Examples 1 to 3, in which a raw material for fluorine doping was used during calcination of the oxide precursor to form a barrier layer on the surface of the lithium manganese-based oxide, it was confirmed that the elution of transition metal from the lithium manganese-based oxide was prevented and at the same time, the particle surface kinetics was improved, thereby showing a better cycle capacity retention rate than Comparative Example 2.

[0258] Experimental Example 5. Experiment on transition metal elution The lithium secondary battery (full cell) manufactured in Manufacturing Example 3 using the positive electrode active materials according to Examples 1 to 3 and Comparative Example 2 was subjected to a formation process of six cycles at 25° C., voltage range of 2.0V to 4.6V, and 0.2C / 0.2C using an electrochemical analyzer (Toyo, Toscat-3100), and then the full cell was charged and discharged for two cycles at 25° C., voltage range of 2.0V to 4.6V, and 0.05C / 0.05C to stabilize it. Next, the full cell was disassembled, and the negative electrode was washed with a diethyl carbonate solvent, vacuum dried at 60° C., and then collected.

[0259] Only the negative electrode active material was separated from the recovered Cu foil (current collector) of the negative electrode, and the separated negative electrode active material was subjected to ICP analysis to measure the Ni and Mn contents contained in the negative electrode active material.

[0260] In addition, the lithium secondary battery (full cell) manufactured in Manufacturing Example 3 using the positive electrode active material according to Examples 1 to 3 and Comparative Example 2 was subjected to a 6-cycle formation process at 25°C, voltage range 2.0V to 4.6V, 0.2C / 0.2C using an electrochemical analyzer (Toyo, Toscat-3100), and then 300 charge / discharge cycles were performed at 25°C, voltage range 2.0V to 4.6V, 1C / 1C. Next, each full cell was subjected to 2 cycles of charge / discharge at 25°C, voltage range 2.0V to 4.6V, 0.05C / 0.05C to stabilize it. Next, the full cell was disassembled, and the negative electrode was washed with diethyl carbonate solvent, vacuum dried at 60°C, and then collected.

[0261] Only the negative electrode active material was separated from the recovered Cu foil (current collector) of the negative electrode, and the separated negative electrode active material was subjected to ICP analysis to measure the Ni and Mn contents contained in the negative electrode active material.

[0262] The measurement results are shown in Table 6 below.

[0263] [Table 6]

[0264] Referring to the results of Table 6, as expected from Experimental Example 4, it can be seen that the rapid deterioration of the life span in Comparative Example 2 was due to the increased content of transition metals deposited on the negative active material after chemical formation or after 300 charge / discharge cycles. In addition, in the cases of Examples 1 to 3, it can be confirmed that the content of transition metals eluted to the negative electrode side is smaller than that in Comparative Example 2 by forming a barrier layer on the surface of the lithium manganese-based oxide.

[0265] Although the embodiments of the present invention have been described above, a person having ordinary knowledge in the art may modify and change the present invention in various ways by adding, changing, deleting or adding elements without departing from the concept of the present invention described in the claims, and this may also be considered to be within the scope of the claims of the present invention.

Claims

1. A positive electrode active material comprising a lithium manganese-based oxide in which a phase belonging to a C2 / m space group and a phase belonging to an R3-m space group are dissolved or combined, The lithium manganese-based oxide includes secondary particles formed by agglomeration of a plurality of primary particles, At least a portion of the oxygen present in the lithium manganese-based oxide is replaced with a halogen, The minor axis length measured on the primary particle exposed on the surface of the secondary particle is greater than 75 nm and less than or equal to 500 nm; a barrier layer that covers at least a portion of the surfaces of the primary particles and the secondary particles is present in the positive electrode active material.

2. 2 . The positive electrode active material according to claim 1 , wherein a ratio of the primary particles having a minor axis length of 100 nm or more among the primary particles exposed on the surfaces of the secondary particles is more than 80% and 100% or less.

3. 2. The positive electrode active material according to claim 1, wherein the average value ([long axis length + short axis length] / 2) of the long axis length and the short axis length of the primary particles exposed on the surface of the secondary particles is 0.1 μm to 5 μm.

4. The positive electrode active material of claim 1 , wherein the lithium manganese-based oxide is represented by the following Chemical Formula 1: [Chemical formula 1] Li(ii a 71 x 72 y )9 2-b 8 b (where: M1 is Mn; M2 is at least one selected from Ni, Co, Al, P, Nb, B, Ti, Zr, Ba, K, Mo, Si, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, V, Ta, Sn, Hf, Ce, Gd, and Nd; X is a halogen capable of substituting at least a portion of the oxygen present in the lithium manganese oxide; 0<a≦0.7, 0<b≦0.1, 0<x≦1, 0≦y<1, 0<x+y≦1.)

5. The positive electrode active material according to claim 1, wherein the lithium manganese oxide is represented by the following chemical formula 1-1: [Chemical formula 1-1] rLi 2 MnO 3-b″ X′ b″ ・(1-r)Li a′ M1 x′ M2 y′ O 2-b′ X b′ (where: M1 is at least one selected from Ni and Mn; M2 is at least one selected from Ni, Mn, Co, Al, P, Nb, B, Ti, Zr, Ba, K, Mo, Si, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, V, Ta, Sn, Hf, Ce, Gd, and Nd, and M2 does not overlap with M1; X and X' are halogens capable of substituting at least a portion of the oxygen present in the lithium manganese oxide, 0<r≦0.7, 0<a'≦1, 0≦b'≦0.1, 0≦b''≦0.1, 0<x'≦1, 0≦y'<1, 0<x'+y'≦1, with the proviso that b' and b'' are not 0 at the same time.

6. The positive electrode active material according to claim 1 , wherein the halogen comprises fluorine.

7. The positive electrode active material according to claim 1 , wherein the barrier layer is present so as to cover at least a portion of a surface of the secondary particles.

8. A grain boundary is defined between adjacent primary particles, The positive electrode active material according to claim 7 , wherein the barrier layer is present in a state of being diffused from a surface portion of the secondary particle toward a center portion of the secondary particle along the crystal grain boundary.

9. The positive electrode active material according to claim 1 , wherein the barrier layer is present so as to cover at least a portion of a surface of the primary particles.

10. 2. The positive electrode active material according to claim 1, wherein the barrier layer comprises at least one selected from a first oxide represented by the following Chemical Formula 2, a second oxide represented by the following Chemical Formula 3, and a third oxide represented by the following Chemical Formula 4: [Chemical formula 2] Li c B d M3 e O f (where: M3 is at least one selected from Ni, Mn, Co, Al, Nb, Ti, Zr, Ba, K, Mo, Si, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, V, Ta, Sn, Hf, Ce, Gd, and Nd; 0≦c≦8, 0<d≦8, 0≦e≦8, 2≦f≦13. [Chemical formula 3] Li g M4 h O i (where: M4 is at least one selected from Ni, Mn, Co, Al, Nb, Ti, Zr, Ba, K, Mo, Si, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, V, Ta, Sn, Hf, Ce, Gd, and Nd; 0≦g≦8, 0≦h≦8, 2≦i≦13, except when g and h are both 0. [Chemical formula 4] Li j M5 k (P l O m ) n (where: M5 is at least one selected from Ni, Mn, Co, Al, Nb, B, Ti, Zr, Ba, K, Mo, Si, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, V, Ta, Sn, Hf, Ce, Gd, and Nd; 0≦j≦10, 0≦k≦8, ​​0<l≦4, 0<m≦10, 0<n≦13, except when j and k are both 0.

Citation Information

Patent Citations

  • Positive electrode active material for lithium secondary battery, production method therefor, and lithium secondary battery containing the same

    JP2015130343A